Situación sociofamiliar e incidencia en la deserción académica en adolescentes de 2do a 3ro de BGU, del colegio Primero de Mayo, Yantzaza Zamora Chinchipe - Román Jaramillo, Cristopher Jhoel (2025)
The objective of this research project is to analyze the socio-family circumstances and their impact on academic dropout, seeking to understand how various external and internal factors can influence the performance and permanence of students in the educational environment. Through a mixed methodological process that includes bibliographic research, which consolidated the conceptualization and contextualization of the related contents, where a solid theoretical basis was configured, technical tools such as the Likert scale questionnaire and the semi-structured interview were applied. This approach helped in the argumentation of various criteria and questions raised about the problem, which facilitated the identification and clarification of the socio-family situation research, and incidence in academic dropout in adolescents from 2nd to 3rd grade of BGU, Primero de Mayo School, Yantzaza Zamora Chinchipe. Thus, it is intended to obtain a clearer vision of the factors that affect dropout, which allowed the formulation of an intervention proposal aimed at reducing this phenomenon, contributing to the academic and personal well-being of students. The research becomes worrisome, since more than half of the 70% of students present conflicts within the home, in such a way that it influences their mood and level of interest towards the educational process and 68% present a moderate risk for academic performance factor for not reaching the average score, while 77% tend to feelstressin conflictsituations. The data obtained allowed to have a clear orientation for the creation of an intervention plan from the role of the social worker, focused on strengthening the psychoemotional support of students and maintaining an effective relationship between parents and their children